Triphenylamine/Tetracyanobutadiene‐Based π‐Conjugated Push–Pull Molecules End‐Capped with Arene Platforms: Synthesis, Photophysics, and Photovoltaic Response. Issue 69 (9th November 2020) - Simón Marqués, Pablo; Castán, José María Andrés; Raul, Benedito A. L.; Londi, Giacomo; Ramirez, Ivan; Pshenichnikov, Maxim S.; Beljonne, David; Walzer, Karsten; Blais, Martin; Allain, Magali; Cabanetos, Clément; Blanchard, Philippe
Abstract: π‐Conjugated push–pull molecules based on triphenylamine and 1, 1, 4, 4‐tetracyanobuta‐1, 3‐diene (TCBD) have been functionalized with different terminal arene units. In solution, these highly TCBD‐twisted systems showed a strong internal charge transfer band in the visible spectrum and no detectable photoluminescence (PL). Photophysical and theoretical investigations revealed very short singlet excited state deactivation time of ≈10 ps resulting from significant conformational changes of the TCBD‐arene moiety upon photoexcitation, opening a pathway for non‐radiative decay. The PL was recovered in vacuum‐processed films or when the molecules were dispersed in a PMMA matrix leading to a significant increase of the excited state deactivation time. As shown by cyclic voltammetry, these molecules can act as electron donors compared to C60 . Hence, vacuum‐processed planar heterojunction organic solar cells were fabricated leading to a maximum power conversion efficiency of ca. 1.9 % which decreases with the increase of the arene size. Abstract : D‐π‐A push–pull molecules based on triphenylamine and 1, 1, 4, 4‐tetracyanobuta‐1, 3‐diene (TCBD) functionalized with terminal arene units strongly absorb in the visible spectrum, but they do not show detectable photoluminescence in solution in agreement with their very short singlet excited state deactivation time. The latter significantly increases in the solid state making TCBD derivatives potential candidates for photovoltaic applications.